2016
DOI: 10.1111/1462-2920.13242
|View full text |Cite
|
Sign up to set email alerts
|

Calcium transcriptionally regulates the biofilm machinery of Xylella fastidiosa to promote continued biofilm development in batch cultures

Abstract: The functions of calcium (Ca) in bacteria are less characterized than in eukaryotes, where its role has been studied extensively. The plant-pathogenic bacterium Xylella fastidiosa has several virulence features that are enhanced by increased Ca concentrations, including biofilm formation. However, the specific mechanisms driving modulation of this feature are unclear. Characterization of biofilm formation over time showed that 4 mM Ca supplementation produced denser biofilms that were still developing at 96 h,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 84 publications
4
31
0
Order By: Relevance
“… –, No changes; Down, downregulated gene expression; Flask, Flask‐RNA‐Seq (Parker et al , ); MC, MC‐RNA‐Seq (this study); and Up, upregulated gene expression. …”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“… –, No changes; Down, downregulated gene expression; Flask, Flask‐RNA‐Seq (Parker et al , ); MC, MC‐RNA‐Seq (this study); and Up, upregulated gene expression. …”
Section: Resultsmentioning
confidence: 63%
“… Comparison of the effect of Ca on gene expression profiles of X. fastidiosa grown in microfluidic chamber (MC‐RNA‐Seq) and batch cultures (Flask‐RNA‐Seq, Parker et al, ). A. Pie charts for distribution of differentially expressed genes (DEGs) in different functional categories between MC‐RNA‐Seq and Flask‐RNA‐Seq.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Parker et al (2016) showed that calcium supplementation changed the global expression of genes that promote continued biofilm development. These genes are related to attachment, motility, exopolysaccharide synthesis, biofilm formation, peptidoglycan synthesis, regulatory functions, iron homeostasis, and phages.…”
Section: Discussionmentioning
confidence: 99%